Analyzing data of social media to evaluate customer behavior of companies using sentiment analysis - Shourin, Bushra; Shawgat, Kazi Sayef; Chowdhury, Serajur Reza (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.